Not Fundamentalist, not Conservative, and not Liberal: The Fundamentals and the Mainstream of American Evangelicalism - Stackhouse, John G. (Christian scholar's review, 2022)
Everyone knows that American Protestantism generally divided into fundamentalist and liberal camps in the 1920s. And many people know that fundamentalism derives from The Fundamentals, early-twentieth-century tracts that reduced the rich doctrinal heritage of Christianity down to five points of do-or-die orthodoxy. Neither of these putative facts, however, is true. This paper shows that The Fundamentals were not fundamentalistic in either respect and that they instead represent the broad mainstream of Anglo-American evangelicalism that continues to this day: not merely conservative, not fundamentalist, and certainly not liberal.